Evaluasi Peranan Layanan Kasir terhadap Kinerja Koperasi dan Kepuasan Anggota pada Koperasi Simpan Pinjam Credit Union Bahtera Sejahtera - Chatrine, Maria Marthina; Mitan, Wilhelmina; Aurelia, Pipiet Niken (Universitas Nusa Nipa Maumere, 2026)
Cashier service plays a crucial role in cooperative operations as it is directly related to members’ financial transactions. Service quality contributes to member satisfaction and loyalty, which in turn affects cooperative performance. This study aims to evaluate the role of cashier services in cooperative performance and member satisfaction at the Koperasi Simpan Pinjam Credit Union Bahtera Sejahtera. A descriptive qualitative approach was employed using observation, interviews, and documentation as data collection techniques. The findings indicate that the cashier service system has generally been implemented well and is positively perceived by members. However, several constraints remain, particularly during peak service hours, including long waiting times caused by the limited number of cashier staff and overlapping responsibilities with customer service functions. These conditions reduce service responsiveness. Nevertheless, cashier services significantly contribute to enhancing member satisfaction and supporting cooperative performance through efficient financial transactions and increased member trust. Improvements in service efficiency and task allocation are therefore recommended to optimize cashier service quality.